Analysis of the Relationship between Early Clinical Factors and Glasgow Outcome Scale in Patients With Traumatic Brain Injury - Wanghan Luo; Xiaoyun Cheng; Weiguo Ying (Brain and Behavior, 2026)
ABSTRACT Objective This study aimed to evaluate the association between early clinical factors and the Glasgow outcome scale (GOS) in patients with traumatic brain injury (TBI). Methods We conducted a retrospective analysis of 98 TBI patients who underwent emergency surgery between January 2021 and January 2024. Based on GOS scores at 6 months post‐surgery, patients were classified into a favorable outcome group (GOS ≥ 4, defined as moderate disability or good recovery, n = 58) and an unfavorable outcome group (GOS < 4, i.e., death, persistent vegetative state, or severe disability, n = 40). Baseline and early clinical parameters were compared between groups. Statistically significant variables from univariate analysis were entered into a multivariate logistic regression model to identify independent prognostic factors. Results Significant intergroup differences were observed in age, time from injury to surgery, bleeding site, midline shift, Glasgow coma scale (GCS) score at admission, blood glucose level, and D‐dimer level (all p < 0.05). Multivariate analysis confirmed that age, time from injury to surgery, GCS score, blood glucose, and D‐dimer level were independent predictors of GOS (all p < 0.05). Conclusion Early clinical factors, including age, time to surgery, GCS score, blood glucose, and D‐dimer level, independently influence GOS in TBI patients. Time from injury to surgery emerged as a potentially modifiable factor in this cohort, suggesting that minimizing delays may improve outcomes.